Practicality Evaluation of an Inquiry-Based Practicum Module on Atomic Structure and Nanomaterials for Vocational Chemistry Learning - Siregar, Rabiyatul Adawiyah; Ubaidah; Zulmiftah; Romadon; Lubis, Armansyah (ICSIGER- International Conference on Science and Emerging Technology, 2025)
This study aims to evaluate the practicality of an inquiry-based practicum module on atomic structure and nanomaterials designed specifically for vocational chemistry learning. Practicality is an essential determinant of whether an instructional product can be implemented effectively, particularly in vocational schools where laboratory time, student readiness, and teacher workload present unique challenges. The research employed an R&D approach focusing solely on the practicality stage using teacher and student questionnaires. Three chemistry teachers and Grade XI vocational students participated in the evaluation. Practicality scores from teachers reached an average of 98.00%, categorized as very practical. Students also rated the module highly, with an average score of 89.13%, categorized as very practical. These findings demonstrate that the module is user-friendly, instructionally feasible, and capable of supporting inquiry-based practicum activities in vocational education. The strong acceptance from both teachers and students indicates that the module is ready for large-scale implementation and future enhancement.